Effects of Mergers. - Cohen, Ruth (Taylor and Francis, 2013)
Effects of Mergers charts the history of six industries with a view to examining the effects of mergers. It deals both with the short and long-term effects of changes in the structure of industry and looks at issues such as whether mergers are in the public interest. The industries covered are: Cement, Textile Printing, Soap, Glass, Motor and Brewing. Some comparative material with industries in the USA is included.